Penerapan Undang - Undang Darurat Nomor 12 Tahun 1951 Tentang Kepemilikan Senjata Api Secara Ilegal: Putusan Nomor 2157/Pid.Sus / 2017/PN. Mdn - Ridwan Harry Simanungkalit; M. Ridwan Lubis (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Law is defined as a rule or norm that must be followed by humans. To ensure the implementation of law in Indonesia, various legal products are needed, especially laws that regulate community activities. Firearms abbreviated as Senpi are weapons that release one or more projectiles that are propelled at high speed by gas produced by the combustion of a propellant (projectile). The problem of ownership to misuse of firearms is something that is very dangerous and high risk, resulting in fatalities in society, the increasing number of cases in recent years in Indonesia shows the importance of the seriousness of law enforcement in responding to this problem. Misuse of Illegal Firearms Ownership is regulated in Emergency Law Number 12 of 1951 concerning the amendment of the